Astral microtubules determine the final division axis of cells confined on anisotropic surface topography. Issue 1 (1st January 2020) - Lee, Kyunghee; Koon, Yen Ling; Kim, Jaewon; Chiam, Keng-Hwee; Park, Sungsu
Abstract: Mitotic spindle orientation is postulated to be regulated by two mechanisms: (1) Hertwig's rule in which cells divide perpendicular to their major axis and (2) cortical cues arising from the spatial distribution of extracellular matrix. It was shown that cortical cues override cell geometry in dictating mitotic spindle orientation for cells cultured on 2D surfaces. In this study, we seek to investigate the interplay between cell geometry and cortical cues in determining mitotic spindle orientation for cells cultured on 3D microgratings. Here, cell geometry is manipulated by culturing RPE-1 and HeLa cells on different micrograting widths while cortical cues are modified by ablating focal adhesion contacts using cytochalasin D. We find a significant correlation between cell aspect ratio and spindle angles. Unexpectedly, disruption of cortical cues through focal adhesion inhibition did not lead to spindle misorientation in both RPE-1 and HeLa. Instead, spindle orientation was perturbed by disruption of microtubules (MTs) to a greater degree than abolishment of cortical focal adhesion cues. These results indicate that cell geometry is more important than cortical cues in maintaining proper spindle orientation and that MTs play an important role in spindle orientation for cells grown on 3D microgratings. To incorporate our findings of cell geometry and MTs as important players in spindle orientation, we developed a computational force balance model that relates both cell elongation, astral MTs to spindle angles and found good agreement between the model and experimental data.